2015
DOI: 10.1111/nmo.12641
|View full text |Cite
|
Sign up to set email alerts
|

Functional dyspepsia and the Rome criteria: a success story

Abstract: The Rome III criteria for functional dyspepsia (FD), published in 2006, immediately generated controversy but have arguably helped to jump start the field in terms of mechanistic and therapeutic research. One controversy has surrounded the veracity of FD symptom subgroups and their overlap. In clinical practice the overlap of postprandial distress syndrome (PDS) and epigastric pain syndrome (EPS) is striking. In this issue, results from Belgium suggest overlap can be reduced by reclassifying those who have pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…In population‐based symptom analyses, dyspeptic symptoms were shown to group around clusters, representing EPS and PDS 3,156 . The literature is divided on the usefulness of distinguishing PDS and EPS for patient management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In population‐based symptom analyses, dyspeptic symptoms were shown to group around clusters, representing EPS and PDS 3,156 . The literature is divided on the usefulness of distinguishing PDS and EPS for patient management.…”
Section: Resultsmentioning
confidence: 99%
“…When the Rome III subdivision is used, a major overlap is found between both, which is largely corrected with the Rome IV subdivision as a good separation between both subtypes is now found both in epidemiological studies and in clinical practice. 3,11,40,[156][157][158] While some studies report different treatment responses, 159,160 others do not. 161,162 To date, no fully published study has evaluated differential pathophysiological mechanisms or treatment outcomes according to the Rome IV subdivision.…”
Section: United European Gastroenterology Journalmentioning
confidence: 99%
“…Adult data suggests that meal-related symptoms, including pain and nausea, may be the norm in FD [ 25 ]. The PDS subtype did have some associations with other GI symptoms in our pediatric cohort, including increased pain with eating (79 %) and weight loss (36 %), as well as a trend toward increased nausea with eating (70 %).…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, overlap between postprandial distress syndrome and epigastric pain syndrome occurs in a large subset of patients . In functional dyspepsia as a group, ingestion of a meal is the most important trigger for symptom occurrence, and we recently showed that adapting the Rome III subdivision by taking into account the meal relationship of functional dyspepsia symptoms reduces the overlap between postprandial distress syndrome and epigastric pain syndrome through an increase in those that can be classified as postprandial distress syndrome …”
Section: Introductionmentioning
confidence: 99%